2010
DOI: 10.1186/1471-2334-10-335
|View full text |Cite
|
Sign up to set email alerts
|

Mycoplasma hominisnecrotizing pleuropneumonia in a previously healthy adolescent

Abstract: BackgroundMycoplasma hominis is a fastidious micro-organism causing systemic infections in the neonate and genital infections in the adult. It can also be the cause of serious extra-genital infections, mainly in immunosuppressed or predisposed subjects.Case PresentationWe describe a case of severe pneumonia and pericarditis due to Mycoplasma hominis in a previously healthy adolescent who did not respond to initial therapy.ConclusionsMycoplasma hominis could be an underestimated cause of severe pneumonia in imm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
1
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 22 publications
0
17
1
1
Order By: Relevance
“…Increasingly, basic and clinical research suggest that urogenital strains of Mycoplasma can cause respiratory disease not just in immunocompromised, but even healthy adults and children and are often not easy to identify or treat 29 . While we did not find a definitive link between the presence of individual organisms and chronic lung disease in this study cohort, patients positive for Mycoplasma 16S DNA were more often asthmatic.…”
Section: Discussioncontrasting
confidence: 75%
See 2 more Smart Citations
“…Increasingly, basic and clinical research suggest that urogenital strains of Mycoplasma can cause respiratory disease not just in immunocompromised, but even healthy adults and children and are often not easy to identify or treat 29 . While we did not find a definitive link between the presence of individual organisms and chronic lung disease in this study cohort, patients positive for Mycoplasma 16S DNA were more often asthmatic.…”
Section: Discussioncontrasting
confidence: 75%
“…It is not clear what role, if any, the urogenital Mycoplasmas and Ureaplasma play in acute or chronic respiratory disease. Increasing evidence suggests that these urogenital Mycoplasmas can be the cause of serious extra‐genital infections, mainly in immunocompromised patients, although extragenital infections are uncommon in healthy patients and cases of pneumonia are exceptional 29 . In recent studies the urogenital Mycoplasmas have been associated with respiratory distress in newborns 30 and neonatal meningitis 31 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mycoplasma are eukaryote commensals and can cause severe pathologies in humans (Uphoff and Drexler, 2005; Myers et al, 2010; Pascual et al, 2010). As shown in Figure 1F, the peptide efficiently cleared mycoplasma from infected eukaryote cell cultures.…”
Section: Resultsmentioning
confidence: 99%
“…MH can cause a wide range of diseases, such as genital infections in adults and may be involved in infections in premature and low birth-weight infants with clinical manifestations of septicaemia (Gonzalez-Jimenez et al , 2006; Karabay et al , 2006; Koshiba et al , 2011). This tiny microorganism can also invade in central nervous system, joint, peritonitis, pyelonephritis and respiratory tract (Garcia et al , 2007; Kacerovsky et al , 2009; Koshiba et al , 2011; Krijnen R. et al , 2006; Myers et al , 2010; Pascual 2010). Barykova (2011) reported that MH infection may be involved in Prostate Cancer development.…”
Section: Introductionmentioning
confidence: 99%